Acute Immune-Mediated Thrombocytopenia due to Oxaliplatin and Irinotecan Therapy - Eric L. Tam; Padma L. Draksharam; Jennifer A. Park; Gurinder S. Sidhu (Case Reports in Oncological Medicine)
We describe a case of a 63-year-old woman with advanced colon cancer and liver metastases who was treated with fluorouracil, leucovorin, and oxaliplatin (FOLFOX) and cetuximab chemotherapy. She tolerated 13 cycles of chemotherapy without any significant hematological side effects, but after the 14th cycle, she developed melena and was admitted for severe thrombocytopenia. After supportive care, the platelet counts rapidly improved to 76,000/μL. Upon initiation of FOLFIRI and cetuximab chemotherapy, she again developed rectal bleeding and severe thrombocytopenia with a platelet count of 6000/μL. Lab testing was positive for oxaliplatin and irinotecan drug-dependent platelet antibodies on flow cytometry assay. Drug-induced thrombocytopenia (DITP) is associated with several classes of drugs with several proposed underlying mechanisms. Prospective studies are needed to further address different mechanisms of drug-induced thrombocytopenia.